One condition of complementability in groups - Malan’ina, G. A.; Chernikov, N. S. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We consider groups satisfying the following condition: Any subgroup of such a group that can be complemented in a larger subgroup can also be complemented in the entire group. A complete description of such groups is obtained under some weak conditions of finiteness.